Symptomatology of COVID-19 - Lessons from a meta-analysis across 13 countries - Gamakaranage, Champika Saman Kumara; Hettiarachchi, Dineshani; Ediriweera, Dileepa; Jayasinghe, Saroj (Asian Journal of Medical Sciences, 2021)
Background: COVID-19 pandemic has resulted in varying clinical manifestations and mortality rates. There is no consensus on the symptomatology that would guide researchers and clinicians. Aims and Objectives: The objective was to identify symptoms and their frequencies of COVID-19 with a meta-analysis of studies from several countries. Materials and Methods: Data sources: A systematic review using PubMed and Google Scholar data sources and reference tracing were used to identify 7176 articles. Eligibility criteria: Suitable articles were selected manually with selection criteria and 14 original articles included in meta-analysis. Data abstraction and analysis: PRISMA guidelines used for data abstraction and a table was generated by feeding it with numbers and proportions of each symptom described. A meta-analysis was carried out using random effect models on each symptom separately across the studies and their prevalence rates and 95% confident intervals were calculated. Results: Selected 14 studies, either cross-sectional or cohort studies are analyzed. There were 2,660 confirmed cases of COVID-19. The majority were from China (n=2,439, 91.7%) and remainder from the Netherlands, Italy, Korea, and India and one article from Europe. There were a total of 32 symptoms identified from the meta-analysis and additional 7 symptoms were identified from reference searching. The most common symptoms were (prevalence >50%): fever (79.56%, 95% CI: 72.17–86.09%), malaise (63.3%, 95% CI: 53.1–73.0%), cough (56.7%, 95% CI: 48.6–64.6%), and cold (55.6%, 95% CI: 45.2–65.7%). Symptoms of intermediate incidence (5–49%) were anosmia, sneezing, ocular pain, fatigue, sputum production, arthralgia, tachypnea, palpitation, headache, chest tightness, shortness of breath, chills, myalgia, sore throat, anorexia, weakness, diarrhea, rhinorrhea, dizziness, nausea, altered level of consciousness, vomiting, and abdominal pain. Rare symptoms (<5%): tonsil swelling, hemoptysis, conjunctival injection, lymphadenopathy, and rash. Conclusion: We found (25/32, from meta-analysis) symptoms to be present in ≥5% of cases which could be considered as “typical” symptoms of COVID-19. The list of symptoms we identified is different from those documents released by the WHO, CDC, NHS, Chinese CDC, Institute Pasteur and Mayo Clinic. The compiled list would be useful for future researchers to document a comprehensive picture of the illness.